Manfaat Aplikasi Mendeley Bagi Mahasiswa dalam Penulisan Karya Ilmiah Mahasiswa Perpustakaan dan Ilmu Informasi Universitas Negeri Padang - Nur Aisah Hasibuan, Rahma; Marlini, Marlini (Universitas Negeri Padang, 2022)
This study aims to determine the benefits of the Mendeley application for students inwriting scientific papers for library and information science students using the ISO/IEC9126-2 Usability measurement method based on the four characteristics as indicators,namely Understandability, Learnability, Operability, and Attractiveness. This study used anexperimental method, namely pre-experimental designs. Pre-Experimental Designs Thisresearch is a design that includes pre-test, treatment and post-test. The population in thisstudy were library and information science students class of 2020. The number of samplesin the study were 47 people. The sampling technique is basic accidental examining(inadvertent inspecting), namely distributing questionnaires to respondents using Googlestructure via the WhatsApp application. The results of the pre-test showed that theunderstanding level of the Mendeley application reached 2.66%, the operability level of theMendeley application reached 2.15%, the learnability level of the Mendeley applicationreached 1.51 %, and the attractiveness of Mendeley applications is 3.11%. The results of thepost test showed that the understanding level of the Mendeley application reached 7.11%,the operability level of the Mendeley application reached 10.4%, the learnability level of theMendeley application reached 3.45 %, and the attractiveness of the Mendeley application is7.55%. From the pre test results, the post test results increase in the utilization andoperation of the Mendeley application. Based on these results it is concluded that theMendeley application has been utilized by users properly.